2009
DOI: 10.1037/a0016091
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of personality in explaining associations between marital quality and parenting.

Abstract: This study examined the contributions of personality to the emotional and behavior dynamics of families. Analyses assessed the degrees to which personality accounts for associations between marital quality and parenting, and mediates genetic contributions to these relationships. Participants included 318 male and 544 female same-sex twin pairs from the Twin and Offspring Study in Sweden. All twins completed self-report measures of marital quality and personality (anxiousness, aggression, sociability). Composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 76 publications
0
23
0
Order By: Relevance
“…Regarding educational attainment, 14.5% of twins and 15.6% of spouses had completed only elementary school; 1.4% of twins and 1.9% of spouses had completed only junior high school/middle school; 28.7% of twins and 26% of spouses had completed two years of senior high school; 11.4% of twins and 15.4% of spouses had completed three or four years of senior high school; 34.1% of twins and 31.7% of spouses had completed college; and 9.9% of twins and 9.4% of spouses reported other levels of educational attainment. There were no differences between MZ and DZ twins in the study in terms of age, highest household occupation level, education, or age of partners (Ganiban et al, 2009). …”
Section: Methodsmentioning
confidence: 78%
“…Regarding educational attainment, 14.5% of twins and 15.6% of spouses had completed only elementary school; 1.4% of twins and 1.9% of spouses had completed only junior high school/middle school; 28.7% of twins and 26% of spouses had completed two years of senior high school; 11.4% of twins and 15.4% of spouses had completed three or four years of senior high school; 34.1% of twins and 31.7% of spouses had completed college; and 9.9% of twins and 9.4% of spouses reported other levels of educational attainment. There were no differences between MZ and DZ twins in the study in terms of age, highest household occupation level, education, or age of partners (Ganiban et al, 2009). …”
Section: Methodsmentioning
confidence: 78%
“…TOSS was reviewed by Institutional Review Boards (IRB) in Sweden and the United States, and all participants provided written informed consent before participating in the study. More detailed information about recruitment, inclusion criteria and other sample description is available elsewhere (Ganiban et al, 2007; 2009; Neiderhiser & Lichtenstein, 2008). The current study included a subset of 876 twin pairs for whom data were complete, including 327 male pairs ( n = 124 MZ pairs; n = 203 DZ pairs) and 549 female pairs ( n = 263 MZ pairs; n = 286 DZ pairs).…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have found strong associations between parent antisocial traits, marital conflict and negative parenting (Cadoret, Yates, Ed, Woodworth, & Stewart, 1995; Connell & Goodman, 2002; Moffitt & Caspi, 2001; Nagin & Tremblay, 2001). There is evidence of a genetic component to this spillover from marital hostility to parenting as data from twin samples reveal personality traits, including aggression, explain 33% to 42% of the covariance between marital quality and parenting for both mothers and fathers (Ganiban et al, 2009). Furthermore, genetically-influenced aggressive personality traits are correlated with conflict in the family (Horwitz, et al, 2010).…”
Section: Importance Of Parent Antisocial Personality Traitsmentioning
confidence: 99%